Chalcogenides as photocatalysts. (15th October 2021) - Rahman, Ashmalina; Khan, Mohammad Mansoob
Abstract : Chalcogenides and chalcogenide-based heterostructures as photocatalysts. Abstract : Chalcogenides are narrow-band gap semiconductors that have been widely used as photocatalysts. These narrow-band gap materials allow more efficient absorption of over 40% of solar energy in the visible light range, which will eventually improve its photocatalytic properties. Under visible light irradiation, these materials generate electron and hole (e − /h + ) pairs. Photo-generated e − /h + pairs have been utilized to split water into hydrogen and oxygen and to remove and degrade industrial, pharmaceutical and agricultural organic/inorganic/biological pollutants that have been accumulated in the environment. In this perspective review, different types of chalcogenides, namely, binary, multinary (ternary and quaternary) and chalcogenide-based heterostructures are presented briefly. This perspective review also highlights the mechanisms involved and remarkable photocatalytic activity enhancement under visible light irradiation that has been widely researched such as the photocatalytic degradation of industrial pollutants and photocatalytic inactivation of bacteria. Lastly, future prospects for the use of chalcogenides as photocatalysts and chalcogenide-based heterostructures were discussed.